REPRESENTASI TOXIC MASCULINITY & BULLYING PADA IKLAN LAYANAN MASYARAKAT KEMENDIKBUD RI “INI GAK LUCU” - Krisna Anjasmani, Rury; Widyananda Putra, Ricky (Universitas Budi Luhur, 2025)
In 2023, toxic masculinity and bullying will become a hot topic of conversation among Indonesian and foreign people. There are many things that influence toxic masculinity and bullying, from the way you dress, speaking style, accessories are a form of communication. Through clothing, a person can convey messages to others. This message is used for imaging or a form of branding of a person himself. Based on this, the author is interested in examining the visual representation conveyed in the public service advertisement (ILM) entitled